Lichtenberg design on side table using acacia wood / Muhammad Toha Azmi - Azmi, Muhammad Toha (Faculty of Applied Sciences, 2019)
Acacia species is a fast-growing tree that usually turns into a waste. Besides, to decrease wastage Acacia tree can be utilized in this project as raw materials. The objective of this research is to produce side table by using Lichtenberg figure using Acacia wood. In addition, to evaluate the customer feedback on quality of side table by using Lichtenberg design. After side table has been produced, a set of questionnaires was distributed to 100 respondents of different gender, age and profession. The characteristic evaluated by respondent include material, design and marketing. Based on customer feedback, most of the respondent agree with the design of the product. The material used also suitable for the function and for the marketing, the product is valuable to be commercialized in the market.